Soil Carbon, Nitrogen Sequestration and Greenhouse Gas Mitigation under Global Change - Zhang, Ling (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Global change induced extreme climate events are becoming more common than ever. Soil carbon and nitrogen pools correlated significantly with changes in atmospheric greenhouse gas. Large increase in atmospheric greenhouse gases, majorly carbon dioxide, nitrous oxide, and methane, can enhance the heating of atmosphere, which will be generally followed by global warming. Mitigation of greenhouse gas emissions including various strategies, such as the sequestrations of carbon and nitrogen in soil, plant or ecosystems, efficient management of agricultural and forestry ecosystems, mitigation of ecosystem carbon and nitrogen leaching, etc. The mitigation of greenhouse gas emissions from all kinds of sources will be therefore crucial in mitigation of global climate change.This reprint gathered latest case studies and methodologies, including, but not limited to measurement and mitigation strategies of carbon and nitrogen pools in soil, plant, or ecosystems, and greenhouse gas emissions, will substantially improve our understanding of the potential, ability, and capacity of ecosystems in mitigation of greenhouse gas emissions and hence global climate change. This reprint can be used by colleagues working on global climate change, ecology, agriculture, forestry and policy makers associated with global change. Chapters included in this reprint were contributed by colleagues from China, Egypt, Italy, Jordan, Mexico, Pakistan, Saudi Arabia, Turkey, etc. It can be used in most countries in the world.